2018
DOI: 10.1016/j.jmb.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

DichroCalc: Improvements in Computing Protein Circular Dichroism Spectroscopy in the Near-Ultraviolet

Abstract: A fully quantitative theory connecting protein conformation and optical spectroscopy would facilitate deeper insights into biophysical and simulation studies of protein dynamics and folding. The web server DichroCalc (http://comp.chem.nottingham.ac.uk/dichrocalc) allows one to compute from first principles the electronic circular dichroism spectrum of a (modeled or experimental) protein structure or ensemble of structures. The regular, repeating, chiral nature of secondary structure elements leads to intense b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…The CD spectra of TH, BH, TF, and BF (Figure 3) showed that all proteins had positive and negative absorption peaks in the 190–202 nm and 202–250 nm wavelength ranges. These absorption peaks are characterized as α‐helix, β‐sheet, β‐turn and random coil, and shifts of these peaks reflect changes in the protein's secondary structure (Jasim et al., 2018). Table 2 shows the secondary structure composition of TH, BH, TF, and BF, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The CD spectra of TH, BH, TF, and BF (Figure 3) showed that all proteins had positive and negative absorption peaks in the 190–202 nm and 202–250 nm wavelength ranges. These absorption peaks are characterized as α‐helix, β‐sheet, β‐turn and random coil, and shifts of these peaks reflect changes in the protein's secondary structure (Jasim et al., 2018). Table 2 shows the secondary structure composition of TH, BH, TF, and BF, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This plot is analogous to Figure 1, as presented by Jasim and co-workers. 57 The near-UV spectrum computed using the X-ray structure underestimates the magnitude of the CD signal found in the experimental spectrum. Two NMR models, frames 3 and 5, are in much better agreement with the experimental spectra, with frame 17 having the least intense negative bands.…”
Section: Recent Computational Studiesmentioning
confidence: 91%
“…55 Vibrational structure is an important, but not the sole, contributor to the bandwidth of transitions. The approach is exactly analogous for the near UV, 56,57 where Li and Hirst have developed new parameters for the Phe, Tyr, and Trp side chains. For near-UV CD spectra, the main focus of interest is the 1 L b and 1 L a transitions.…”
Section: Recent Computational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a change of the α-helical structure content of prion protein during hydrogel formation was reported [45] and for BSA a specific change of its secondary structure and folding stability was reported upon addition of PEG [46]. Near-UV CD spectroscopy generally provides a distinct tertiary structure “fingerprint”, which is specifically sensitive to aromatic amino acids and disulfide bonds [47]. BPTI consists of 58 amino acids, containing four tyrosine residues in total, three of them are part of two neighboring β-sheet regions supporting intermolecular interactions [48].…”
Section: Resultsmentioning
confidence: 99%